APPLIED MODEL STUDY COOPERATIVE TYPE TPS (THINK-PAIR-SHARE) TO INCREASE INTERACTION STUDY OF STUDENT IN SMA NEGERI 8 PADANGSIDIMPUAN - Muhammad Darwis (Ristekdik : Jurnal Bimbingan dan Konseling, 2019)
Abstract: This research find solution to increase study result from student class XI SMA Negeri 8 Padangsidmpuan, with experiment study with applied cooperative type TPS (Think-Pair-Share) accurated,with experiment research.The goals from this research to know increase interaction and result study of student is teached with lecture garrulous and applied cooperative study type TPS (Think-Pair-Share) in matery to class XI SMA Negeri 8 Padangsidimpuan. Research do to student class XI SMA Negeri 8 Padangsidimpuan. As total population are 100 students,as sample 80 students is class XI-2 as method lecture garrulous study,class X1-3 as method  study cooperative type TPS (Think-Pair-Share).Hipotesis in this research : applied study model cooperative type TPS (Think-Pair-Share) can increasing interaction result study in lesson to student class XI SMA Negeri 8 Padangsidmpuan. Instrument with test.Analysis with use trying test.Result of research that : average pre-test student is teached with using cooperative type TPS (Think-Pair-Share) before lesson is teached with using cooperative study type TPS (Think-Pair-Share) before lesson is teached is much 61,458 after giving lesson get average result of study (post-test) 79,5,get increase average 18,1.Applied study with method lecture garrulous get average result study (post-test) totally 67,6 there is increase average totally 13,7.Result of observation study with using model study cooperative type TPS (Think-Pair-Share).Interaction study is good (82,66).Applied study cooperative type TPS (Think-Pair-Share) can increase interaction study ,structure concept of plant to student class XI SMA Negeri 8 Padangsidimpuan.